Developmental trajectory of communication repair in children with Fragile X Syndrome. (February 2020) - Fielding-Gebhardt, Heather; Warren, Steven F; Brady, Nancy C
Background and aims: The development of communicative competence requires both language and social skills. The ability to repair following a communication breakdown is critical for continued conversational interchange and to ensure comprehension of bids for communication. Communication repair demonstrates adequate language and social skills. Children with Fragile X Syndrome have difficulty with language development and social skills, which may result in delays or deficits in repair. Repair may be additionally impaired in children with Fragile X Syndrome and co-morbid autism. This study examined the development of repair in children with Fragile X Syndrome from toddlerhood into middle childhood. Methods: Fifty-five children with Fragile X Syndrome and their biological mothers participated. Data were collected during in-home visits approximately every 18 months. Videotaped mother–child interactions were collected, as well as standardized assessments of language, social skills, and autism symptomology. Results: Children with Fragile X Syndrome acquired the ability to repair at 90% mastery by three-and-a-half years of age. Multilevel logistic regressions predicting probability of repair indicated marginally significant effects of mean length of utterance and number of different words, and significant effects of global social skills and autism symptomology. Effect sizes were small to moderate. Conclusions: Ability to repair was measured in a naturalistic setting, which allowed children with Fragile X Syndrome to utilize repairs in their daily interactions. Although children with Fragile X Syndrome may have delayed development of repair relative to typically developing expectations, in general they nonetheless catch up and demonstrate a robust ability to repair by three-and-a-half years of age. However, this study provides evidence that individual differences in language and social skills may influence ability to repair in children with Fragile X Syndrome. Finally, the relationship between autism symptoms and repair remains unclear, necessitating further exploration. Implications : Given the noted delay in repair in young children with Fragile X Syndrome, clinicians working with this population should target development of this skill as early as possible to maximize successful social interactions. This may be particularly necessary for children with Fragile X Syndrome and co-morbid autism.